ПОРІВНЯЛЬНИЙ АНАЛІЗ ЧИСЕЛЬНОГО ТА ЧИСЕЛЬНО-АНАЛІТИЧНОГО МОДЕЛЮВАННЯ ГЕНЕРАТОРІВ З ПОСТІЙНИМИ МАГНІТАМИ - Кондратенко, І.П.; Гребеніков, В.В.; Гамалія, Р.В.; Крищук, Р.С. (Інститут електродинаміки НАН України, Київ, 2026)
The paper investigates the adequacy of a simplified mathematical model of a numerical-analytical method for calculating low-power permanent magnet generators for autonomous power systems operating with a rectifier and active load. The object of study is generators with a radial arrangement of permanent magnets on the rotor surface. The model considered is based on an idealized representation of the air gap between the rotor and stator and does not take into account the tooth-and-groove structure, the actual geometric dimensions of the permanent magnets, and the nonlinear magnetic properties of ferromagnetic materials. To assess the adequacy of the model, a comparative analysis of the results of numerical-analytical calculations with the data of high-precision modeling using the finite element method in the Ansys Maxwell software package was performed. A series of FEM models of generators with varying levels of detail and complexity were was constructed. The paper presents mathematical expressions of the numerical-analytical method based on the Fourier transform, oriented towards computer implementation. The modeling was performed taking into account the electrical circuit of the generator, which includes a three-phase rectifier and an active load. The time dependencies of the magnetic field distribution and electromagnetic torque were calculated. The errors in the calculation of the electromagnetic torque obtained by the numerical-analytical method were determined in comparison with FEM models of varying degrees of detail. The results demonstrate the capabilities and limitations of the simplified mathematical model and confirm the feasibility of its use for preliminary calculations and optimization of the parameters of permanent magnet generators for autonomous renewable energy systems. References 12, figures 6, tables 3.